2006
DOI: 10.1002/chem.200500676
|View full text |Cite
|
Sign up to set email alerts
|

A Macrocycle/Molecular‐Clip Complex that Functions as a Quadruply Controllable Molecular Switch

Abstract: Herein, we report the synthesis of a molecular clip with TTF side-walls and its binding behavior towards electron-deficient guests, namely the formation of macrocycle/molecular-clip supramolecular complexes in solution. Four different sets of external stimuli--the K(+)/[2.2.2]cryptand, NH(4) (+)/Et(3)N and (p-BrPh)(3)NSbCl(6)/Zn pairs, and heating/cooling cycles-control the movement of this molecular switch between its threaded and unthreaded states and provide color changes that are observable by the naked ey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…Studying the glycoluril-based molecular clip 15 presenting also TTF sidewalls [ 56 57 ], Chiu et al have observed the mixed-valence and radical cation dimer states at high concentration (10 −3 M) and at room temperature [ 58 ]. Indeed, the CV of molecular clip 15 exhibited four consecutive oxidation waves, which were interpreted by a succession of oxidation processes of the TTF sidewalls ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Studying the glycoluril-based molecular clip 15 presenting also TTF sidewalls [ 56 57 ], Chiu et al have observed the mixed-valence and radical cation dimer states at high concentration (10 −3 M) and at room temperature [ 58 ]. Indeed, the CV of molecular clip 15 exhibited four consecutive oxidation waves, which were interpreted by a succession of oxidation processes of the TTF sidewalls ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TTF has proved to be a near-ideal molecular component in such systems. It has been exploited in the design of many different supramolecular architectures, including molecular machines, molecular flasks, , molecular tweezers, and molecular switches. …”
Section: Introductionmentioning
confidence: 99%
“…It has been established that the donor-acceptor interactions between TTF and bipyridinium units become weakened in less polar solvents owing to the decreased strength of the pstacking interaction. [14] The decomplexation of 1 a and 1 b was substantially slower in less polar solvents than in polar solvents, suggesting that the increase of the free energy of the CT state from a polar solvent to a less polar solvent was considerably smaller than the increase of the free energy of activation for the extrusion of the CBPQT 4+ ring over the foldamer segment caused by the enhancement of their intramolecular hydrogen bonds in less polar solvent.…”
mentioning
confidence: 99%